Strategi Promosi Digital Berbasis Influencer untuk Meningkatkan Daya Saing UMKM: Studi Kasus PT. Seduh Boga Sejahtera (Oncil) - Aprianti, Vika; Badriyah, Ratnaini; Sutisna, Hadiya Wildan (LPPM UNIBI, 2023)
This Community Service activity aims to assist PT. Seduh Boga Sejahtera, the owner of the Oncil beverage brand, in developing an effective digital promotion strategy through collaboration with influencers. Oncil is a small and medium enterprise (SME) based in Bandung Regency that offers beverages with a fresh brewed concept, positioning itself as a budget drink with premium taste. Facing intense competition, Oncil encounters challenges such as limited business networks, weak branding, and declining profits. The proposed solution involves leveraging digital platforms like Instagram and TikTok for product promotion through influencers with extensive reach to enhance brand awareness and attract more customers. This strategy is expected to expand Oncil's market, increase sales, and help the SME survive and grow amidst the dynamics of the beverage industry.